2022
DOI: 10.32604/phyton.2022.020323
|View full text |Cite
|
Sign up to set email alerts
|

Positive Effects of Biochar on the Degraded Forest Soil and Tree Growth in China: A Systematic Review

Abstract: Soil degradation threatens the forest sustainable productivity, particularly in afforestation system. Biochar derived from agroforestry waste or biomass can potentially improve the degraded forest soil and promote the tree growth. To expand the application of biochar for forestry productivity improvement, we here reviewed the effects and the underlying mechanisms of biochar on the degraded forest soil and tree growth. Totally 96 studies that conducted from pot to field investigations in China were summarized. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 105 publications
0
2
0
Order By: Relevance
“…This is because the different textures of the soil determine the function of the biochar once it was incorporated into the soil. Generally speaking, sandy soils have more grit, larger porosity and higher water holding capacity [ 131 ]. Ghorbani et al [ 132 ] reported that applying 1% and 3% RHB to sandy soils increased the cation exchange by 20% and 30%, respectively.…”
Section: Rice Husk Biochar As a Soil Conditionermentioning
confidence: 99%
“…This is because the different textures of the soil determine the function of the biochar once it was incorporated into the soil. Generally speaking, sandy soils have more grit, larger porosity and higher water holding capacity [ 131 ]. Ghorbani et al [ 132 ] reported that applying 1% and 3% RHB to sandy soils increased the cation exchange by 20% and 30%, respectively.…”
Section: Rice Husk Biochar As a Soil Conditionermentioning
confidence: 99%
“…Under the background of soil BC improvement [ 18 ], in this paper, we focus on the effect of fertilization conditions on fertile black soil and strive to provide practical suggestions for soil improvement in black soil areas. A high proportion of BC applications has previously been considered to be impractical or economically infeasible [ 19 ].…”
Section: Introductionmentioning
confidence: 99%